Neonatal Cerebral Venous Thrombosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The clinical presentation and management of 7 neonates with idiopathic cerebral venous thrombosis (CVT) are reported from the Floating Hospital for Infants and Children, New England Medical Center Hospitals, Tufts University School of Medicine, Boston, MA.